Al di qua della pulsione di potere. Derrida, Freud e la società delle pulsioni - Vitale, Francesco (Bollettino Filosofico, 2021)
The essay focuses on the Derridian definition of «drive for power (Bemächtigungstrieb)» proposed at the end of To Speculate – on “Freud”, a text published in The Postcard (1980) that comes from the seminar La vie la mort, held in 1975-1976 and published in April 2019. It is first of all about making clear the distance that Derrida takes from Freud, in particular with respect to the hypothesis advanced by the latter of a death drive as an irreducible motive of living beings and consequently of psychic life, and more precisely with respect to what, according to Freud, follows from this hypothesis, namely an original cruelty that would condition human life, individual and collective. Secondly, it is a matter of bringing out, through the deconstruction of the «drive for power (Bemächtigungstrieb)» the Derridean conception of the psychic system as a «society of drives». Keywords: Death Drive, Deconstruction, Drive for Power, Psychoanalysis, Teleology